(untitled) (Innovate Conferences, 2025)
The Turanians, a vast region of diverse ethnic groups speaking Turkic and Persian languages, located in Central Asia, have made significant contributions to world civilization throughout history. This article analyzes the cultural development of the Turanians, their influence in the fields of trade, art, science, and philosophy. The economic networks and cultural exchanges they created established contacts with other cultures through the ancient Silk Road. The artistic, scientific, and philosophical heritage of the Turanians is of great importance not only regionally but also globally. This study examines the contribution of the Turanians to world civilization and sheds light on their influence on modern culture.